INNOVATION MANAGEMENT TO CREATE A GROWING COMPANY BY USING A MEMBER CARD AT NATASHA MILK SHOP - Toto.Hermanto, Toto.Hermanto (Universitas Utpadaka Swastika, 2023)
ABSTRACT Every year the development of technology is getting faster and every year many companies develop technology from small companies to bona fide companies. Natasha's milk shop is a company that has only started pioneering since 2010 so there are many problems starting with the absence of member cards for consumers, member cards aim to provide promos, discounts and points for every product sales transaction to consumers who shop and with the member card, both parties are mutually beneficial between consumers and companies, member cards also function as branding media, branding media when consumers feel many benefits from using member cards, consumers want to shop and use member cards again. Natasha milk shop companies do not apply member cards If the member card does not exist this is a very serious problem and must be addressed immediately by the natasha milk shop company, the development of technology that cannot be utilized properly by the natasha milk shop company so that there are problems that must be overcome. So with this peniliti want to discuss, innovate and find solutions for the progress of the company natasha milk shop, the purpose of this study wants to make an innovation in the development of technology by making application-based applications so that readers understand the procedures for use from starting member card registration to using member cards in the application. After the application has been developed, the company gives questions to consumers, these questions are to provide the extent of the System Usability Scale for the company. After the System Usability Scale is carried out the results of 15 respondents form 1315: 15 = 88 then for the total calculation of 88, (70 - 90 Good Exellent).